1998
DOI: 10.1046/j.1365-4362.1998.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythema multiforme, Stevens–Johnson syndrome and toxic epidermal necrolysis in northeastern Malaysia

Abstract: This study shows that drugs remain the commonest culprit in SJS and TEN. Despite adequate treatment, the mortality rate remains high, especially in TEN. These findings are similar to those of other reported studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 17 publications
4
47
3
2
Order By: Relevance
“…In opposite, in the series of Pitche et al in Togo [11] and Mame Thierno et al in Senegal [5], antiretroviral drugs have not been found, which can be due to the fact that in Togo, despite the high prevalence of HIV infection no HIV-infected patients in this country was on antiretroviral treatment (for economic reasons, the majority of HIV-infected patients did not yet have access to antiretroviral drugs in Africa) [11]. In contrast to our study and those of European authors, several sub-Saharan African authors [5] [10] [16] reported a high incidence of anti TB drugs in the development of SJS/TEN. The frequency of tuberculosis reflects the prevalence of anti TB drugs in these countries such as Guinea.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…In opposite, in the series of Pitche et al in Togo [11] and Mame Thierno et al in Senegal [5], antiretroviral drugs have not been found, which can be due to the fact that in Togo, despite the high prevalence of HIV infection no HIV-infected patients in this country was on antiretroviral treatment (for economic reasons, the majority of HIV-infected patients did not yet have access to antiretroviral drugs in Africa) [11]. In contrast to our study and those of European authors, several sub-Saharan African authors [5] [10] [16] reported a high incidence of anti TB drugs in the development of SJS/TEN. The frequency of tuberculosis reflects the prevalence of anti TB drugs in these countries such as Guinea.…”
Section: Discussioncontrasting
confidence: 85%
“…• 5% (1/22) in Malaysia [16]. The major problem remains the sequelae, which are common and can involve the functional prognosis and seriously affect the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies enumerating medications specifically associated with SJS have identified antibiotics, anticonvulsants, and nonsteroidal anti-inflammatory drugs. 10,11,[13][14][15][16] A recent multinational case-control study in Europe called EuroSCAR (European Study of Severe Cutaneous Adverse Reactions) showed a high risk of SJS with the following medications: trimethoprim-sulfamethoxazole and other anti-infective sulfonamides, lamotrigine, carbamazepine, phenytoin, phenobarbital, allopurinol, nevirapine, and oxicam nonsteroidal anti-inflammatory drugs. 13 Among recently marketed drugs, nevirapine and lamotrigine were strongly associated with SJS, with sertraline showing a lower but still significant risk as well.…”
Section: Discussionmentioning
confidence: 99%
“…16,[22][23][24][25] SJS and TEN are severe cutaneous adverse reactions (SCAR). [26][27][28][29][30][31][32][33][34] Epidermal detachment below 10% is defined as SJS, whereas it is considered TEN above 30% [35,36]. Epidermal detachment between 10% and 30% defines transitional SJS/TEN.…”
Section: Introductionmentioning
confidence: 99%